Additional record of Termitomyces heimii, Kokrajhar, Assam, INDIA - Rava, Mamoni; Ali, Raju; Boro, Hankhray; Das, Sandeep (Mushroom Research, 2018)
Termitomyces genus is known for its distinct relationship with termites (Macrotermitinae) for their symbiotic interaction. The group appeared as monophyletic and belongs to Tricholomataceae family. The mushroom sample collection was carried out during monsoon season (April-August 2017) in community managed forest of Shorea robusta trees. The taxonomy work has been done by studying the habitat notes, macro and micro morphological characters. The present study revealed the sample to be Â Termitomyces heimii.